Grammatical Roles and Relations of Batak Toba Language: Typology Study - Simanjuntak, Tarida Alvina; Mulyadi, Mulyadi (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The aim of this paper is to discuss about grammatical relation in Batak Toba language. The problem will be discussed is word order, case marking, and semantic role in Batak Toba language. Therefore, the purpose of the paper is to determine the relation of grammatical in Batak Toba language, and it is observed from word order, case marking, and semantic role. Data collection is take from written language and spoken. The result of discussion to point out that the word order in Batak Toba language have form P-S-O. This point supported by the kind of diathesis in Batak Toba Language is active diathesis, passive diathesis, and reflexive diathesis. In order that, the product of discussion point out that grammatical relation and semantic role in Batak Toba Language is S = A / P and S = P / A. The meaning of this point is Batak Toba language make the same relation with S is A and S is P. The form of grammatical relation and semantic role prove that Batak Toba language have the pattern case marking is nominative-accusative and ergative absolutive.